2021
DOI: 10.15585/mmwr.mm7041a2
|View full text |Cite
|
Sign up to set email alerts
|

Binge Drinking Among Adults, by Select Characteristics and State — United States, 2018

Abstract: Excessive alcohol use includes binge drinking, heavy drinking (i.e., 15 or more drinks per week for men; eight or more drinks per week for women), and any drinking by pregnant women or persons aged <21 years. https://www.cdc. gov/alcohol/fact-sheets/alcohol-use.htm † https://www.thecommunityguide.org/topic/excessive-alcohol-consumption § https://www.uspreventiveservicestaskforce.org/uspstf/recommendation/ unhealthy-alcohol-use-in-adolescents-and-adults-screening-and-behavioralcounseling-interventions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 10 publications
0
30
0
Order By: Relevance
“…The use of alcohol, and binge drinking more specifically, are common behaviours in the USA. A recent report found that during 2018, 16.6% of US adults reported binge drinking in the past 30 days 26. Given the strong relationship between alcohol use, and particularly alcohol use disorder and alcohol intoxication, and TBI,20 this puts millions of adults at increased risk of sustaining a TBI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of alcohol, and binge drinking more specifically, are common behaviours in the USA. A recent report found that during 2018, 16.6% of US adults reported binge drinking in the past 30 days 26. Given the strong relationship between alcohol use, and particularly alcohol use disorder and alcohol intoxication, and TBI,20 this puts millions of adults at increased risk of sustaining a TBI.…”
Section: Discussionmentioning
confidence: 99%
“…We calculated mean level of binge drinking across all waves; data on binge drinking was collected in 1982–1985, 1988–1989, 1992, 1994, 2002 and every 2 years starting in 2006 until 2014. Of note, this definition of binge drinking differs from the Centers for Disease Control and Prevention’s definition (four or more drinks for women and five or more drinks for men on one occasion); the implications of which are discussed in the Limitations section 26…”
Section: Methodsmentioning
confidence: 99%
“…They are then inevitably ingested by humans because they are present in daily food items such as coffee [ 3 ], baked food [ 4 ], bakery products [ 5 , 6 ], roasted meat [ 7 ], pizza [ 8 ], and especially, beer [ 9 , 10 ], the most consumed alcoholic beverage worldwide. Over the past 50 years, total global beer consumption has risen sharply in emerging economies [ 11 , 12 ]. Long-term, excessive beer consumption has been associated with metabolic disease outcomes (obesity, diabetes and non-alcoholic fatty liver disease) and causes preventable death [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a recent study has found that heavy drinking during early adulthood to midlife years was associated with increased risk for AD ( Langballe et al, 2015 ). The majority of individuals that binge-drink are in late adolescent to mid-life years (18–44 yo) and “age-out” of heavy drinking, with low rates in aged populations ( Bohm et al, 2021 ). This suggests that these epidemiological findings in humans could be due to persistent effects of binge ethanol during young adulthood to midlife years that increase risk for AD.…”
Section: Introductionmentioning
confidence: 99%